The Ohio Canals : Second Edition - Wilcox, Frank N. (Frank Nelson), 1887-1964 (Book collections on Project MUSE., 2015)
From Cleveland to Portsmouth and Toledo to Cincinnati, two great canals and numerous connections and feeders laced Ohio with a thousand miles of waterways in the years before the Civil War. They were a major force in transforming Ohio from a frontier society to a leading agricultural and commercial state, but they were doomed by the arrival of the railroads. Today, they are all but vanished, except for the preservation efforts of some historical societies. The Ohio canals live again through the eye and hand of artist-historian Frank N. Wilcox. From his years of walking the canal ways and explo.